Nas redes do "telejornalismo policial" cearense : uma análise etnográfica do fazer jornalístico - Morales, Luciana Pinho (2020)
The growing number of episodes of violence in Brazilian cities has been gaining great prominence in the mass media, especially on television, making room for the creation of an extensive national “programing” dedicated almost exclusively to the dissemination of news related to police actions and practices. A similar phenomenon can be observed in the context of Ceará, in which “TV police newscast” broadcasted by television stations located in Fortaleza disputes the audience's daily attention, totaling about thirteen hours of “police news” on broadcast TV only in the State of Ceará. Given this context, this study aims to understand the way in which interpersonal practices and relationships between journalists and other social actors involved develop behind the scenes of these media productions, seeking to describe and analyze, through an ethnographically inspired analysis, the self-perceptions that the examined “police journalists” have about themselves, the feelings of belonging that they have in relation to their profession and the frames that guide their logics of actions and ways of thinking about the “violence” and “criminality” phenomena and about their authors. The empirical research was made possible through comprehensive interviews and field observations carried out with journalists who work or worked on local “TV police newscast”, by monitoring their work routines, both in “newsrooms” and outside, seeking to know their professional trajectories and the netting of relationships and reciprocity in which they participate, in order to understand how they work in practice. From the collected empirical data, I realized the existence of complex relationships net that are developed in the journalistic universe examined, deeply based on the constant mutual exchange of information, favors etc. between “police journalists”, police officers and other public agents, advertisers/sponsors from different social segments (businessmen, political parties, religious groups etc.) and the “public”. I also identified in the reports of the observed journalists a set of knowledge, values and ideologies that, together, characterize the ways in which “police journalists” compose the frames that guide the productive process of “TV police newscast”.